2019
DOI: 10.1124/jpet.119.257345
|View full text |Cite
|
Sign up to set email alerts
|

δ-Tocopherol Effect on Endocytosis and Its Combination with Enzyme Replacement Therapy for Lysosomal Disorders: A New Type of Drug Interaction?

Abstract: Induction of lysosomal exocytosis alleviates lysosomal storage of undigested metabolites in cell models of lysosomal disorders (LDs). However, whether this strategy affects other vesicular compartments, e.g., those involved in endocytosis, is unknown. This is important both to predict side effects and to use this strategy in combination with therapies that require endocytosis for intracellular delivery, such as lysosomal enzyme replacement therapy (ERT). We investigated this using d-tocopherol as a model previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 84 publications
(157 reference statements)
1
2
0
Order By: Relevance
“…In addition, staining of CAD-treated cells with the PLD detection reagent LipidTOX Red (Figure B and Figure S4A) revealed that 20 μM LOP treatment induced an accumulation of lipids in vesicular structures, whereas the same concentration of KET did not. In line with previously documented data on the functional inhibition of ASM, LOP-treated H1299-WT cells (as well as cells treated with 6 other “CAD-hit” compounds) also showed a higher green fluorescent signal when stained overnight with BODIPY FL C12-sphingomyelin, in contrast to 20 μM KET treatment (Figure S4B), which indicates reduced sphingomyelin degradation due to ASM inhibition. Similarly, only LOP exposure could visually increase the cytosolic delivery of Cy5-labeled siRNA, as evident from Figure C. Upon treatment with 20 μM LOP, ∼38% of the cells showed a diffuse cytosolic siRNA fluorescence in contrast to the untreated and KET-exposed cells where a punctate pattern, indicative of lysosomal sequestration, was observed.…”
Section: Resultssupporting
confidence: 86%
“…In addition, staining of CAD-treated cells with the PLD detection reagent LipidTOX Red (Figure B and Figure S4A) revealed that 20 μM LOP treatment induced an accumulation of lipids in vesicular structures, whereas the same concentration of KET did not. In line with previously documented data on the functional inhibition of ASM, LOP-treated H1299-WT cells (as well as cells treated with 6 other “CAD-hit” compounds) also showed a higher green fluorescent signal when stained overnight with BODIPY FL C12-sphingomyelin, in contrast to 20 μM KET treatment (Figure S4B), which indicates reduced sphingomyelin degradation due to ASM inhibition. Similarly, only LOP exposure could visually increase the cytosolic delivery of Cy5-labeled siRNA, as evident from Figure C. Upon treatment with 20 μM LOP, ∼38% of the cells showed a diffuse cytosolic siRNA fluorescence in contrast to the untreated and KET-exposed cells where a punctate pattern, indicative of lysosomal sequestration, was observed.…”
Section: Resultssupporting
confidence: 86%
“…Human iPS-NSCs can be exploited to define novel therapeutic strategies counteracting substrate accumulation in affected lysosomes. For example, studies on hiPS-NSCs proposed a complementary approach based on tocopherols to stimulate the exocytosis of macromolecules via the phagocytic, caveolae-, clathrin-, and cell adhesion molecule (CAM)-mediated pathways to restore the endosomal-lysosomal trafficking ( Xu et al, 2012 ; Manthe et al, 2019 ). Both δ- and α-tocopherol significantly reduced the storage in NPC and NPA hiPSC-derived NPCs and neurons ( Yu et al, 2014 ; Long et al, 2016 ), in agreement with previous observations showing that α-tocopherol-rich diet increases the survival of Purkinje neurons, reduces astrogliosis, and improves coordination and locomotor functions in NPC mouse models ( Marin et al, 2014 ).…”
Section: Hipsc-derived Nscs To Develop New Therapeutic Strategiesmentioning
confidence: 99%
“…The exact mechanism of action is unclear, but it was reported that tocopherol isomers evoked fast Ca 2+ responses with an increase in cytosolic Ca 2+ [20]. It was also shown that tocopherol caused exocytosis of related vesicles, such as endocytic ones [21]. Cyclodextrins, on the other hand, have been shown to create "holes" in membrane structures by extracting cholesterol from membranes, and these disruptions in the plasma membrane are normally repaired in cells by lysosomal exocytosis [22].…”
Section: Introductionmentioning
confidence: 99%